Analisis Makna Ganda Muraadif dan Musytarak dalam Implikasi Hukum - Marwah, Andi; F, Fatmawati; Amin, Abd. Rauf (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The application of the Muraadif and Musytarak lafaz requires in-depth study according to the demands of the increasingly developing times, to review the meanings of the lafaz in the text so that it remains relevant to the conditions of society. Therefore, this article specifically discusses lafaz studies related to the meaning of Muraadif and Musytarak. To achieve significant research results, the method used in this research is data collection techniques through literature study. The research results show that the study of Muraadif and Musytarak pronunciations in texts has a crucial role in the study of Islamic Law, especially in understanding the Al-Qur'an and Hadith. This research aims to explore the meaning and implications of Islamic law. Lafaz Muraadif is used to provide semantic variations that enrich meaning and adapt language style to certain contexts. Meanwhile, the Musytarak pronunciation is often a source of differences in interpretation, because its meaning is very dependent on the context of its use. The application of Muraadif in the text aims to emphasize spiritual and legal messages, while the application of Musytarak requires deeper context analysis. The implications of this study indicate that a misconception of Muraadif and Musytarak can result in differences in the interpretation of Islamic Law. Thus, this study contributes to the development of the science of tafsir and fiqh, especially in the differences in interpretation that arise due to variations in meaning in language. Abstrak : Penerapan lafaz Muraadif dan Musytarak memerlukan kajian yang mendalam sesuai tuntutan zaman yang kian berkembang, untuk meninjau kembali makna-makna lafaz dalam teks agar tetap relevan dengan kondisi Masyarakat. Oleh karena itu, artikel ini membahas secara khusus kajian lafaz terkait makna Muraadif dan Musytarak. Untuk mencapai hasil penelitian yang signifikan, metode yang digunakan dalam penelitian ini adalah teknik pengumpulan data melalui studi pustaka. Hasil penelitian menunjukkan bahwa kajian mengenai lafaz Muraadif dan Musytarak dalam teks-teks memiliki peranan yang krusial dalam studi Hukum Islam, terutama dalam memahami Al-Qur’an dan Hadis. Penelitian ini bertujuan untuk menggali makna serta implikasi hukum Islam. Lafaz Muraadif digunakan untuk memberikan variasi semantik yang memperkaya makna dan menyesuaikan gaya bahasa dengan konteks tertentu. Sementara itu, lafaz Musytarak sering kali menjadi sumber perbedaan dalam penafsiran, karena maknanya sangat bergantung pada konteks penggunaannya. Penerapan Muraadif dalam teks bertujuan untuk menekankan pesan-pesan spiritual dan hukum, sedangkan penerapan Musytarak memerlukan analisis konteks yang lebih dalam. Implikasi dari kajian ini menunjukkan bahwa pemahaman yang salah terhadap Muraadif dan Musytarak dapat mengakibatkan perbedaan dalam penafsiran Hukum Islam. Dengan demikian, penelitian ini berkontribusi pada pengembangan ilmu tafsir dan fikih, khususnya dalam perbedaan interpretasi yang muncul akibat variasi makna dalam bahasa.